1998
DOI: 10.4269/ajtmh.1998.59.893
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in biochemical characters of Brazilian field populations of the Leishmania vector, Lutzomyia longipalpis (Diptera: Psychodidae).

Abstract: Abstract. The phlebotomine sand fly Lutzomyia longipalpis is the insect vector of visceral leishmaniasis, a protozoan disease of increasing incidence and distribution in Central and South America. Electrophoretic allele frequencies of 15 enzyme loci were compared among the L. longipalpis populations selected across its distribution range in Brazil. The mean heterozygosity of two colonized geographic strains (one each from Colombia and Brazil) were 6% and 13% respectively, with 1.6-1.9 alleles detected per locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
3
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 40 publications
6
46
3
2
Order By: Relevance
“…Phylogenetic analysis (MP) reveals close relationships among populations in the Brazilian highlands (Lapinha Cave), the Amazon (Salvaterra and Santarem), San Francisco Basin (Jacobina) and Brazilian scrubland (Baturité). These results are concordant with patterns of divergence in the nuclear genome (isozyme variation) among the same Brazilian populations, with the exception of the population at Roraima, that was not included in the isozyme studies (Mukhopadhyay et al, 1998;Mutebi et al, 1999;Azevedo et al, 2000). These authors concluded that populations in Brazil represent a single species, but with relatively high levels of genetic divergence among local populations.…”
Section: Vicariance Hypothesissupporting
confidence: 69%
“…Phylogenetic analysis (MP) reveals close relationships among populations in the Brazilian highlands (Lapinha Cave), the Amazon (Salvaterra and Santarem), San Francisco Basin (Jacobina) and Brazilian scrubland (Baturité). These results are concordant with patterns of divergence in the nuclear genome (isozyme variation) among the same Brazilian populations, with the exception of the population at Roraima, that was not included in the isozyme studies (Mukhopadhyay et al, 1998;Mutebi et al, 1999;Azevedo et al, 2000). These authors concluded that populations in Brazil represent a single species, but with relatively high levels of genetic divergence among local populations.…”
Section: Vicariance Hypothesissupporting
confidence: 69%
“…Colonies of L. longipalpis have been successfully established before (Sherlock & Sherlock 1959, Killick-Kendrick et al 1977, Ready 1978,1979, Modi & Tesh 1983, Buescher et al 1984. L. longipalpis populations from Central and South America show a great polymorphism in behavior, morphology and biochemical characters (Ward et al 1983, Hamilton et al 1996, Dujardin et al 1997, Mukhopadhyay et al 1998a, b, Dias et al 1998, Yin et al 1999. These results either lead L. longipalpis differences to be suspected as due to a complex of cryptic species (Lanzaro et al 1993, Warburg et al 1994 This work was partially supported by Capes (MSc scholarship to JFLM) and by the State Government of Roraima.…”
Section: Methodsmentioning
confidence: 99%
“…Variability in tergal spot morphology is believed to be a polymorphic character not related to genetic isolation (Mukhopadhyay et al 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of such cryptic species in Brazil was disputed by Mukhopadhyay et al (1998), Mutebi et al (1999), Azevedo et al (2000), and Arrivillaga et al (2002Arrivillaga et al ( , 2003 who considered that there is only a single species in that country, based on a study of several widely separated populations for genetic variability in biochemical characters. They felt that the reasons for any epidemiological variations in AVL should be sought elsewhere.…”
Section: Lu Longipalpis: the Major Vector Of Avlmentioning
confidence: 99%